Effect of various heat treatment on physical and chemical characteristics of red rice bran (Oryza nivara L.) Rojolele. (October 2019) - Siswanti,; Anandito, R B K; Nurhartadi, E; Iskandar, B D
Abstract: This research aims to study the effect of various heat treatment on physical and chemical characteristics of red rice bran ( Oryza nivara L.) Rojolele. This study used a Completely Randomized Design (CRD) with one-factor variations of heat treatment applied on the bran. The various heat treatments use Oven an hour (80ºC and 100ºC), Microwave maximum temperature (2 and 5 minutes), and Autoclave 150 0 C (5 and 10 minutes). Results showed that all heat treatment methods decrease L value. The highest moisture level is on heating by microwave for 2 min. There were no significant difference in the level of ash, fat, and antioxidant activity. The FFA content was decreased by all heating treatment. The fenol level with heating with Oven 80ºC an hour was the highest. Among the treatments, Oven an hour at 80ºC is the best method. This method produces red rice bran with characteristics of lightness, water content, ash, fat, protein, total phenol, antioxidant activity, crude fiber, and free fatty acid content respectively 49.78; 5.51%; 8.37%; 27.11%; 10.50%; 0.25%; 75.88%; 9.30%; and 13.48%. Red rice bran Rojolele also contains anthocyanin and thiamin obtained from spectroscopy FTIR.